Analisis Terciptanya Transisi Kepemimpinan Baru Dalam Perhelatan Pilkada Ponorogo Dilihat Dari Perspektif Masyarakat - Abduh Budiarso; Jusuf Harsono (Jurnal Pemerintahan dan Politik, 2021)
The implementation of the Ponorogo regional election in 2020 is indeed in a special atmosphere, considering that two competitor pairs of candidates are fighting for people’s sympathies in order to grab seat number 1 in Ponorogo. In welcoming the people’s democratic party, the hot atmosphere is identical to be found in the field. Regional election is a prestigious event to determine the fate of the region for the next 5 years, so that all parties are competing to give their best. In Ponorogo, both of successful team and volunteers from both pairs of candidates showed enthusiasm and support in many ways interestingly, the competition in the Ponorogo regional election was between two old competitors namely Sugiri Sancoko VS Ipong Muchlissoni where in the previous regional election (2015) had heated up to a dispute over the election results. A new chapter has begun, but the atmosphere of competition is certainly more heated for both sides. The leadership note of the regent of Ipong Muhclissoni is a major highlight, which has been felt by the people of Ponorogo through experience and understanding over the past 5 years. This researches aims to narrow the perspective of society, so that it provides a concrete picture of two possibilities, namely: the emergence of a new leader, or retaining an old leader. Because officially in the Ponorogo regional election in 2020 there are only two candidates, it is very interesting to conduct this research.          Keywords : Transition, Leadership, Regional Election